Village Development through Potential Analysis of Kaliagung Village, Kapanewon Sentolo, Kulon Progo Regency, Special Region of Yogyakarta - Rubiyatno Rubiyatno; Agnes Maria Polina; Lucia Kurniawati; A. Prasetyadi; Achilleus Hermawan Astyanto; Hirmawan Wijanarka; Maria Vincentia Eka Mulatsih (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to determine the potential of Kaliagung Kapanewon Sentolo Village, Kulon Progo Regency, Special Region, it is hoped that with the identification of this, the researcher can formulate a roadmap for the development of Kaliagung Kapanewon Sentolo Village, Kulon Progo Regency, Special Region of Yogyakarta. This research is a qualitative descriptive research. The population in this study is the leaders and community leaders of all community members in Kaliagung Village, Kapanewon Sentolo, Kulon Progo Regency, Special Region of Yogyakarta. The data collection method uses observation, focus discussion groups and literature studies are used to obtain information about the potential of the village, qualitative descriptive analysis specifically using the analysis of strengths, weaknesses, opportunities, and threats. SWOT analysis contributes to the development of strategic management theory, especially in the context of independent village development. The SWOT analysis shows that this framework can be applied effectively in the context of village development. This approach helps to link between internal conditions (local resources) and external conditions (government and market support) in the formulation of development strategies. The results of the EFE and IFE analysis placed the Kaliagung Village in a certain quadrant, which provided a theoretical basis for choosing the most suitable strategy, such as a growth-oriented strategy .